(untitled) (GEOMATE Journal, 2020)
The utilization of exhaust gas flow with Electric Turbo Compounding (ETC) mechanism is applied on this research. On this mechanism, the exhaust gas flow is used to rotate the alternator. The ETC installation is designed to prevent the produce of a back pressure effect which disturbs the engine performance. This mechanism was chosen based on literature study that had been done previously to the exhaust gas flow utilization mechanism on several vehicles. As the result, the ETC mechanism is the most suitable to be developed on passenger vehicles with small capacities. The power transfer process on ETC uses a gear mechanism with 2:1 ratio to increase input rotation of the generator. From the test result, the charging current is 1.25-1.48 A at 850-2.000 rpm engine speed. It is such a quite low number when compared to the normal charging system, which is 6.23 – 8.1 A at 1.200 – 2.000 rpm engine speed. Nevertheless, for the waste energy utilization, this number is much more promising to be developed in the future. From the result of this research, it is known that the installation of the ETC mechanism can be a solution for vehicle’s wasted energy utilization on exhaust gas flow form even the amount of flow generated is small.